Perilaku Konsumen Dalam Ekonomi Berbagi: Analisis Bibliometrik dan Tinjuan Literatur Sistematis - Dewantara, Norman; Noer, Lissa Rosdiana (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
The current research investigates consumer behaviour in the sharing economy, including consumer preferences, factors that influence consumer decisions, as well as economic and social impacts of the sharing economy. The established process for conducting bibliometric analysis and systematic literature review is the PRISMA protocol which found as many as 59 relevant articles. The research trend occurred from 2015 to 2023 where the average increase was 31.61% every year. Barnes, S.J. and United Kingdom became the most prolific writer and country. The co-occurrence shows that sharing economy and collaborative consumption are related to consumer behaviour and consumption. The systematic literature review shows consumer behaviour in the sharing economy is influenced by social, economic, and technological factors. Sharing platforms also encourage consumer preferences for collaborative consumption. Further research can explore tax practices, regulations, and the long-term impact of the sharing economy.